Osteosarcoma Therapy: Inhibition of CaMKIIα Activity Enhances Antitumor Effect of Fullerene C60 Nanocrystals by Suppression of Autophagic Degradation (Adv. Sci. 8/2019). Issue 8 (17th April 2019) - Xu, Jing; Wang, Hongsheng; Hu, Yi; Zhang, Yu Shrike; Wen, Longping; Yin, Fei; Wang, Zhuoying; Zhang, Yingchao; Li, Suoyuan; Miao, Yanyan; Lin, Binhui; Zuo, Dongqing; et al.
Abstract : In article number1801233, Jianxun Ding, Yingqi Hua, Zhengdong Cai, and co‐workers report a combination strategy for improving the efficacy of fullerene C60 nanocrystals in anti‐osteosarcoma therapy. Inhibition of CaMKIIα activity by KN‐93 promotes excessive autophagosome accumulation and autophagic degradation blockage through lysosomal dysfunction induction and further upregulates the anti‐osteosarcoma effect of fullerene C60 nanocrystals.